Inhabiting the “Resurrectiform” God: Death and Life as Theological Headline in Paul - Boakye, Andrew K. (The expository times, 2016)
Scholarly evaluations of how Paul interpreted the ‘Christ event’ within his arguments routinely compartmentalize the crucifixion and the resurrection, placing the weight of emphasis on the former. Whilst never explicitly denying the critical significance of the resurrection, the appraisals of certain commentators often seem to limit the import of the event to a vindication of Jesus’ ministry, in view of its seemingly ignominious climax. The Pauline lexicon of revivification, however, makes the validity of such a stance questionable and opens the possibility that both elements of the Christ event influenced Pauline thought in ways obscured by the tendency to undervalue the implications of Jesus’ resurrection. A consideration of the distribution and functionality of the ‘death and life’ language in the Pauline corpus, illustrates the weightiness which the apostle attaches to the concept of death reversed by life. By applying such an understanding to 2 Corinthians, this paper will consider how readings of Paul might be enhanced by reassessing the impact of death and new life operating in tandem.